2015
DOI: 10.3389/fpls.2015.00713
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed seed aging responsive heat shock protein OsHSP18.2 implicates in seed vigor, longevity and improves germination and seedling establishment under abiotic stress

Abstract: Small heat shock proteins (sHSPs) are a diverse group of proteins and are highly abundant in plant species. Although majority of these sHSPs were shown to express specifically in seed, their potential function in seed physiology remains to be fully explored. Our proteomic analysis revealed that OsHSP18.2, a class II cytosolic HSP is an aging responsive protein as its abundance significantly increased after artificial aging in rice seeds. OsHSP18.2 transcript was found to markedly increase at the late maturatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 76 publications
2
84
0
Order By: Relevance
“…A small heat shock protein, limHSP16 .45 from David lily overexpressed in Arabidopsis confers tolerance to heat, salinity and oxidative stress28. Arabidopsis overexpressing OsHSP18.2 demonstrated high seed vigor, and longevity by reducing ROS accumulation in seed and better performance of seed in germination under abiotic stresses29.…”
Section: Resultsmentioning
confidence: 99%
“…A small heat shock protein, limHSP16 .45 from David lily overexpressed in Arabidopsis confers tolerance to heat, salinity and oxidative stress28. Arabidopsis overexpressing OsHSP18.2 demonstrated high seed vigor, and longevity by reducing ROS accumulation in seed and better performance of seed in germination under abiotic stresses29.…”
Section: Resultsmentioning
confidence: 99%
“…However, overexpression of AsHSP17 , a new sHSP gene from creeping bentgrass ( Agrostis stolonifera ), negatively regulate plant responses to adverse environmental stresses in transgenic A. thaliana 22 . Recently, OsHSP18.2, a sHSP from rice ( Oryza sativa ), was shown to play important roles in seed vigor, longevity and seedling establishment in transgenic A. thaliana 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Manipulating HSFA9 expression highlighted the overall importance of sHSPs for desiccation tolerance and seed longevity [31,32]. More recently, [33] demonstrated that overexpressing a rice sHSP in Arabidopsis seeds improved seed vigour and longevity and was beneficial for seedling establishment under stress conditions.The effect of heat shock on sHSPs oligomerization has been widely investigated in microorganisms [34], animals [35], and plants [5,36]. Different mechanisms of heat-induced activation have been proposed: dissociation of sHSP multimers into smaller species (monomer to tetramers), increased rates of subunit exchange, as well as other conformational changes [5].…”
mentioning
confidence: 99%
“…Manipulating HSFA9 expression highlighted the overall importance of sHSPs for desiccation tolerance and seed longevity [31,32]. More recently, [33] demonstrated that overexpressing a rice sHSP in Arabidopsis seeds improved seed vigour and longevity and was beneficial for seedling establishment under stress conditions.…”
mentioning
confidence: 99%